Expressing a logic problem in terms of NAND

colerelm

New member
Joined
Oct 24, 2011
Messages
33
I was told that ANY logic expression can be expressed using solely AND and NOT (therefore NAND). How would I convert (((A & B) or (B & ~C)) or ~D) & E) to an expression using the connective NAND? Or, more generally, how do you express complicated statements such as the one mentioned into equivalent statements using the connective NAND?
 
I was told that ANY logic expression can be expressed using solely AND and NOT (therefore NAND).
Here are the basics.
\(\displaystyle \left( {p \vee q} \right) \equiv \neg \left( {\neg p \wedge \neg q} \right)\)
and
\(\displaystyle \left( {p \to q} \right) \equiv \neg \left( {p \wedge \neg q} \right)\)

With those two, we can do any others.
 
Here are the basics.
\(\displaystyle \left( {p \vee q} \right) \equiv \neg \left( {\neg p \wedge \neg q} \right)\)
and
\(\displaystyle \left( {p \to q} \right) \equiv \neg \left( {p \wedge \neg q} \right)\)

With those two, we can do any others.


Thank you. That's exactly what I was looking for.
 
Top